Follow-up of hereditary endometrial carcinoma caused by MLH3 gene mutation: a case report - Zhang, Changlin; Ye, Jiaying; Li, Qiaqia; Zhan, Jijie; Yang, Dong; Li, Jundong; Li, Tian; Wan, Ting (Frontiers in Oncology, 2025)
BackgroundEndometrial cancer is a common cancer in women, partially linked to defects in mismatch repair function. Besides the well-known mismatch repair proteins, the MLH3 gene may also contribute to cancer susceptibility.Case presentationIn this case report, we reported that two related mothers and daughters had mutations in some of their germline genes, with MLH3 as a possible low-risk gene for endometrial cancer, which we further explored as contributing to the development of endometrial cancer.ConclusionsThis case identifies germline heterozygous mutations in two patients, suggesting a potential role for MLH3 in endometrial carcinogenesis, which may act as a low-risk factor to increase the risk of tumor susceptibility and does not rule out the possibility of synergistic increases in pathogenicity with other genes.